Production of tetrathionate hydrolase by thiobacillus ferrooxidans devulcanization of ground tire rubber - Emeliana binti Othman (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Among all of the devulcanization methods ofspent rubber introduced, enzymatic devulcanization is a much safer and preferred choice because it does not include any harmful or toxic chemicals, and is normally not energy intensive. The process of enzymatic devulcanization was carried out by exposing the surface of a vulcanized rubber piece to at least one enzyme, secreted from chemolithoautotrophic iron- and sulfur-oxidizing bacterium to break the sulfur bonds in the vulcanized rubber structure, rendering it more acceptable to be recycled. Increased in the accumulation of waste tires in the landfills not only consumed large area but has also increased the potential for large fires which are extremely detrimental to the environment. This study aims to evaluate the usage of tetrathionate hydrolase enzyme for devulcanization of ground tire rubber (GTR). Design of experiments and the analysis of data obtained were conducted using Design Expert® version 6.0.8 software in determining the optimal medium composition and physical condition for production of tetrathionate hydrolase from Thiobacillus ferrooxidans. The analysis was done by initial screening of parameters and medium components that influence the production of tetrathionate hydrolase using Plackett Burman followed by one-factor-at-a-time (OFAT) to determine the optimum range and the final optimization procedure was done using Response Surface Methodology (RSM). It was found that the optimum condition for achieving maximum tetrathionate hydrolase activity was obtained using agitation of 156 rpm, pH 3.49 and inoculum size of 1010 cells/mL producing 1.205 U/mL of enzyme activity. The optimized condition was utilized for the production of tetrathionate hydrolase that was then used for devulcanization of GTR whereby the factors involved such as time of incubation, concentration of enzyme and concentration of rubber was studied using OFAT and further evaluated using Face Centered Central Composite Design (FCCCD) under RSM. In this stage, the devulcanization was aimed to oxidize sulfide bonds up to sulfoxide and sulfone only, by halting further degradation to sulfate. The analysis using FCCCD revealed that the minimum conversion to sulfate was found after two hours of incubation using 4.62 % of rubber with only 1.6987 mg/mL of sulfate released. In the final stage, the devulcanized rubber was added to virgin rubber at 1;4 ratio for the revulcanization process, followed by mechanical properties testing.A significant improvement could be seen in the tensile strength, elongation at break and other mechanical properties of the newly revulcanized rubber compared to the untreated control sample. The overall study showed that enzymatic devulcanization of spent rubber using tetrathionate hydrolase is possible and could be a better option for sulfur oxidation making it more acceptable for recycling. Future study could be done by conducting the devulcanization of rubber using purified enzyme.